Fiqh-us-seerah : understanding the life of prophet Muhammad - Ghazali, Muhammad, 1917- (Riyadh : International Islamic Federation of Student Organizations, IIFSO : Distribution by International Islamic Pub. House, 2005)
Includes bibliographical references.